## Side, Angle, and, (Ex)-Circle

For discussing Olympiad level Geometry Problems
sowmitra
Posts: 155
Joined: Tue Mar 20, 2012 12:55 am

### Side, Angle, and, (Ex)-Circle

In $\triangle ABC$, $\angle A=2\angle C$. $(O)$ is its $A-$excircle, and, $M$ is the mid-point of $AC$. $OM\cap BC=D$. Show that,
$[1]$ $AD$ bisects $\angle OAC$
$[2]$ $BA=BD$
"Rhythm is mathematics of the sub-conscious."
Some-Angle Related Problems;

tanmoy
Posts: 289
Joined: Fri Oct 18, 2013 11:56 pm

### Re: Side, Angle, and, (Ex)-Circle

sowmitra wrote:. $(O)$ is its $A-$excircle
I don't understand this line.Please clarify it.
"Questions we can't answer are far better than answers we can't question"

photon
Posts: 186
Joined: Sat Feb 05, 2011 3:39 pm
Location: dhaka
Contact:

### Re: Side, Angle, and, (Ex)-Circle

$O$ is the centre of the excircle opposite to $A$ , to match with notations used in books , $O=I_A$
Try not to become a man of success but rather to become a man of value.-Albert Einstein

Tahmid
Posts: 110
Joined: Wed Mar 20, 2013 10:50 pm

### Re: Side, Angle, and, (Ex)-Circle

[1]
Let $AD\cap OC=N$
For triangle $\Delta AOC$ ;
$\frac{AP}{PO}\cdot \frac{ON}{NC}\cdot \frac{CM}{MA}=1$ [ceva]
or, $\frac{AP}{PO}=\frac{NC}{NO}$

Now let $I$ be the incentre of triangle $\Delta ABC$ ...... $\therefore I\epsilon AP$
$(A,I,P,O)$ harmonic
$\therefore \frac{AI}{IP}=\frac{AO}{PO}$
or,$\frac{AO}{PO}=\frac{AC}{CP}$ [angle bisector theorem]
or,$\frac{AO}{PO}=\frac{AC}{AP}$ [$CP=AP$ because $\angle A=2\angle C$]
or,$\frac{AP}{PO}=\frac{AC}{AO}$

$\therefore \frac{NC}{NO}=\frac{AC}{AO}$ [$=\frac{AP}{PO}$]
So, from the converse of angle bisector theorem ; $AD$ bisects $\angle OAC$

[2]
$\angle BAD=\angle BAP\angle PAD=\angle C+\frac{\angle C}{2}$
$\angle BDA=\angle DCA+\angle DAC=\angle C+\frac{\angle C}{2}$
$\angle BAD=\angle BDA$
So, $BA=BD$

tanmoy
Posts: 289
Joined: Fri Oct 18, 2013 11:56 pm
photon wrote:$O$ is the centre of the excircle opposite to $A$ , to match with notations used in books , $O=I_A$
Thanks for clarify it.BTW,here is a very easy solution of part $1$:
Let $AO\cap BC=U$.Join $O,C$.By $\text{Menelaus's theorem}$ we get,$\frac{AO}{OU}\times \frac{UD}{DC}\times \frac{CM}{MA}=1$.Or,$\frac{AC}{CU}\times \frac{UD}{DC}=1$.Or,$\frac{UD}{DC}$=$\frac{CU}{AC}$.
Now,$AU=UC$.$\therefore$ $\frac{UD}{DC}$=$\frac{AU}{AC}$.
By the $\text{Converse of Angle Bisector Theorem}$,$AD$ bisects $\angle OAC$.